The Correlation Between Students’ Grammar Ability and Students’ Speaking Ability in SMP Panca Budi Medan - Madina; Cindy Angelina Gulo; Sikkop Rehulina Br Gurning; Theo Angelios Simanungkalit; Mestina Br Gea (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this study is to establish the correlation between grammar ability and speaking ability. There were 30 students of ninth grade at SMP Panca Budi Medan who were the study’s subjects. Study’s correlational design incorporates quantitative research. Cluster random sampling was utilised to collect the necessary data for the research. Two different instruments were used to evaluate the students' abilities. The variables in question are the independent variable (X) and the dependent variable (Y), with X representing grammar ability and Y representing speaking ability. The data for this study were gathered in two stages. The first involved grammar test using 25 multiple-choice grammar question using google form and the second was a speaking test using direct speaking by telling best experience. Statistic called statistical analysis or inferential statistics in SPSS 26 version were used to perform quantitative analysis. The data analysis revealed a noteworthy association between the grammar proficiency and speaking skills of ninth-grade students at SMP Panca Budi Medan. According to the findings from the analysis conducted using SPSS 26 version and presented in table 4, there was a strong positive correlation of 0.823 between students' grammar skill and students' speaking ability. Futhermore, the two pieces of information were related